Designing Pension Systems with Coherent Funded Private Pillars Including Issues for Notional Defined Contribution Schemes - Price, William (World Bank, Washington, DC, 2018)
This paper reviews the factors that should guide the design of private funded pensions to create a complete pension system alongside a notional defined contribution—or public—component. It argues that a mix of public and private pensions is the most effective option to deliver the best combination of pension outcomes. Pension design should start with a vision for five core outcomes: coverage, adequacy, sustainability, efficiency, and security. Thinking through these outcomes helps guide choices for market structure, benefit type, contributions, investment strategy, and other factors. As well as technical design, the governance, scale, and expertise of pension funds are critical for good investment and other outcomes. Regulators and supervisors should also focus on these outcomes and then work out how best to mitigate the risks to achieving them over time. These issues are relevant in relation to any public pillar, but notional defined contribution (NDC) systems bring clarity and transparency to policy makers in the benefit formula. The NDC payout formula can offer insights for how to improve the payout options in funded pillars. The clarity on the NDC formula also means that the joint distribution of public and private pensions can be modeled. This is important because the precise NDC formula may have implications for optimal investment strategies for private pensions, given, for example, the negative correlation between real per capita GDP growth and equity market returns over long periods.